Strategi Kantor Pos dalam Meningkatkan Kualitas Pelayanan Perspektif Ekonomi Islam - Muhammad Ardy; Selviani Selviani (AL-Muqayyad, 2022)
This research is motivated by the application of service quality carried out by a company engaged in the service sector is to provide the best quality service for consumers with the aim of creating customer satisfaction. Of course, to implement good service quality there must be strategies carried out by the post office. The purpose of this study is to determine the Strategy of the Salak River Branch Post Office in Improving Service Quality. This research is qualitative research. The results showed that the strategy of the Salak River branch post office in improving the quality of service was not fully in accordance with the teachings of Islam. It can be seen from the strategies that have been carried out only on the right strategy and communication, but the implementation of the mandate strategy which should be a trustworthy strategy is also important to make people more interested in using post office services. Thus, it can be concluded from the results of the study that the strategy of the Sungai Salak branch post office in improving service quality is not fully in accordance with the teachings of Islam.